LEARNING MANAGEMENT ON BUDDHISM COURSE IN THE LEARNING AREA OF SOCIAL STUDIES, RELIGION AND CULTURE FOR THE THIRD YEAR SECONDARY SCHOOL STUDENTS IN SECONDARY SCHOOLS IN NAM PHONG DISTRICT, KHON KAEN PROVINCE - Dhirabhaddo (Khantamala), PhraYodchay; Saengsai, Prayoon; Ruangsan, Niraj (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were: to study the condition of learning management and to study guidelines for promoting the learning management of Buddhism course in the learning area of Social Studies, Religion and Culture Learning Group for the third-year secondary school students in 10 secondary schools in Nam Phong District, Khon Kaen Province. This study was carried out by means of the mixed research methods: quantitative and qualitative. The number of samples used in the research was 50, and that of the target group was 10. The research tools were questionnaires and interviews used in collecting data. The statistics used to analyze the obtained data were: Frequency, Percentage, Mean and Standard Deviation. The research results were as follows: 1) The condition of learning management in the learning area of Social Studies, Religion and Culture Learning Group for the third-year secondary school students in 10 secondary schools in Nam Phong District, Khon Kaen Province in overall was at the highest level. The studied aspects were ranked from ‘learning management activities’, followed by ‘learning management’, ‘curriculum’, ‘assessment and evaluation’ and ‘media for learning management’. 2) The guidelines for promoting learning management are as follows: the curriculum should contain up-to-date content for today’s society; the learning management should always be integrated with new things; the learning management media should be diverse and equipped with modern equipment; in terms of learning management activities, teachers should provide opportunities for students to express opinions and organize appropriate activities for learners, while assessment and evaluation should promote various and actual assessments.